Pemanfaatan Sereh (Cymbopogon Citratus) Dengan Pendekatan Molekuler Sebagai Pestisida Organik Untuk Alternatif Pengendalian Serangga - Nurriani, Ameilisa Eka; Nabila, Aulia Siska; Alamsyah, Azizah Athiyyah; Oktavia, Nadya Putri; Beliani, Nuriyah Nanda; Cahyaningrum, Oktavia Fajar; Putriku, Rachel Lintang; Lestari, Mastuti Widi; Adi, Omry Tri Asmara (Forum Kerjasama Pendidikan Tinggi, 2025)
The presence of pests or insects around settlements is the main factor that people often use household pesticides kill insects. Uncontrolled use of household pesticides can cause health problems and can cause the risk of poisoning in humans. Lemongrass contains compounds that are anti-insect. The content of compounds contained in lemongrass is effective as an organic pesticide that can minimize the uncontrolled use of household pesticides. The purpose of this activity is to provide insight and understanding to the community about the use of organic pesticides from lemongrass plants as an alternative to controlling residential insects. The implementation method in the Community Health Service Program (PPKM) is carried out by providing counseling on the use of lemongrass plants to be used as organic pesticides as an alternative to controlling insects and showing demonstration videos of making organic pesticide products from lemongrass plants. Based on the results of the T-test analysis on pretest and post-test values, Asymp. Sig was obtained at 0.007, where 0.007<0.05, which means that the pretest and post-test values are significantly different. The results indicate an increase in participant’s knowledge before and after the education. It is hoped that participant can use lemongrass as an environmentally friendly organic pesticide.